Biochar-assisted rapid formation of core–biofilm anammox granules via interfacial trapping of extracellular polymeric substances - Jingwei Fu; Yue Li; Yaqian Liu; Can Xiong; Pei Li; Xuanqi Long; Qian Li; Rong Chen (Bioresource Technology, 2026)

Basal heave stability analysis of braced excavations in layered cohesive-frictional soils with a discretization-based kinematic mechanism - Chenzhi Fu; Maosong Huang; Jingwei Zhang; Zhenhao Shi; Zhongjie Zhang (Transportation Geotechnics, 2026)

ERα-mediated endoplasmic reticulum stress drives 4-tert-octylphenol–induced cardiac developmental toxicity in zebrafish - Jin Chen; Mingxue Gong; Jing Fu; Yan Liu; Jingwei Lei; Ruixi Liu; Mengqin Wu; Ying Lei; Anfei Liu; Tao Jing; Zhenzhong Liu (Environmental Pollution, 2026)

NOX4/Keap1/Nrf2/ROS signaling drives ferroptosis in trimethyltin chloride-induced cardiac developmental malformations - Jin Chen; Hanwen Hu; Jing Fu; Yaolin He; Hui Zhou; Jingwei Lei; Ming Huang; Jianqi Wang; Anfei Liu; Zhenzhong Liu (Toxicology, 2026)

The value assessment framework and institutional innovation for implementing the requisition-compensation balance policy of natural coastline in China - Yue Yu; Yanyan Fu; Wei Liu; Degang Jiang; Jingwei Zhang; Xingmin Liu; Xueping Wei; Jing Lin (Frontiers in Marine Science, 2026)
Natural coastlines are vital for ecological security and sustainable development. To mitigate their decline, China has implemented requisition-compensation balance policy (RCBP) for coastlines, adapted from the management of cultivated land. This study systematically reviews the policy’s institutional evolution and highlights fundamental distinctions between coastlines and cultivated land in functional services, spatial heterogeneity, and evaluation standards. While the policy has achieved preliminary success in maintaining quantitative and qualitative balance, several challenges persist. These include the absence of functional equivalence assessment, weak long-term safeguards, underdeveloped cross-regional and market-based coordination mechanisms. These gaps risk leading to “higher-grade requisition, lower-grade compensation” and ecological degradation at compensation sites, and increased administrative burdens. To address these issues, this study develops a comprehensive value-equivalence compensation framework structured around a “three-dimensional and four-layer” indicator system that integrates functional, spatial, and temporal dimensions. It advocates for a strategic transition from quantity-oriented to value-oriented governance. Corresponding policy recommendations are proposed: establishing unified technical guidelines for value assessment, creating a nationwide quota-trading platform to activate market forces, and strengthening post-restoration monitoring for long-term stewardship. This research provides theoretical and practical insights to enhance the protection, restoration and sustainable management of coastlines in China.

TRA: Topological Relation-Aware link prediction in spatial knowledge graphs - Fu Zhang; Qinghui Li; Hongzhi Chen; Tong Shen; Jingwei Cheng; Weijun Li (Earth Science Informatics, 2026)

Curvature sensing strategy for flexible gripper fingers during grasping deformation: enabling in-orchard online apple size grading - Guangze Zhao; Hongjian Zhang; Jingwei Sun; Huawei Yang; Shaowei Wang; Shuangxi Liu; Xinpeng Cao; Shenghui Fu; Yongxian Wang; Linlin Sun; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Electrospray-designed Al microspheres with dual-functional binders: Synergistic energetic-azide/Al-fluorination for enhanced combustion - Jiaqi Wei; Yuhang Wang; Xiaolong Fu; Yong Kou; Xiaoyan Zhang; Shixuan Wu; Jingwei Hao; Wei Jiang; Guangpu Zhang (Chemical Engineering Journal, 2025)

Accelerating light-driven bioreaction with interfacial engineered microalgae-bacteria consortia: Unraveling positive charge-mediated biological interaction - Haixing Chang; Xueqing Gui; Meina Han; Jingwei Fu; Liandong Zhu; Shih-Hsin Ho (Chemical Engineering Journal, 2025)

Arabidopsis phytyl ester synthases PES1 and PES2 moonlighted as xanthophyll acyltransferases in plants - Jingwei Fu; Katie D. Heiden; Laura S. Bailey; Kari B. Basso; Bala Rathinasabapathi (Planta, 2025)

Effects of dissolved oxygen on the anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal (AOA-SNDPR) process for advanced wastewater treatment and in situ sludge reduction - Baokun Xu; Liang Liu; Meng Wang; Zhidong Fu; Peng Xu; Jingwei Ma; Qiulai He (Journal of Environmental Chemical Engineering, 2025)

Precipitation versus dissolution at the phosphorus and Solanum nigrum L. root exudate interface: Implications for lead rebound in rhizosphere soils - Jingwei Zhang; Hao Shi; Yiquan Xing; Yixin Chen; Jiacheng Li; Haojie Fu; Guoqing Dai; Zhaojie Cui; Lei Wang; Xinxin Li (Science of The Total Environment, 2024)

Oxysophocarpine attenuates inflammatory osteolysis by modulating the NF-κb pathway and the reactive oxygen species-related Nrf2 signaling pathway - Xiaofeng Shi; Tian Gao; Chaohong Yu; Shaotian Fu; Tingxian Guo; Wei Xu; Xiaojun Li; Yitian Wang; Jingwei Zhang; Xinlin Jia; Yuanqing Mao (Inflammopharmacology, 2024)

Deciphering mechanism of sulfide stress on microalgae and overcoming its inhibition by regulation growth acclimatization period - Hongyan Peng; Jingwei Fu; Yun Huang; Ao Xia; Xianqing Zhu; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2024)

Induction of Phosphorylated Tau Accumulation and Memory Impairment by Bisphenol A and the Protective Effects of Carnosic Acid in In Vitro and In Vivo - Shaoi Hsu; Huichi Huang; Chunhuei Liao; Hsiyun Huang; Yachen Shih; Jingwei Chen; Hanting Wu; Tzuyu Kuo; Ruhuei Fu; Chiawen Tsai (Molecular Neurobiology, 2024)

Proliferating cell nuclear antigen of Ulva prolifera is involved in the response to temperature stress - Hongyan He; Juanjuan Yang; Yuan He; Xiuwen Yang; Caiwei Fu; Dongren Zhang; Jingwei Dong; Aurang Zeb; Jing Qu; Songdong Shen (Journal of Oceanology and Limnology, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Biochar’s role to achieve multi-pathway nitrogen removal in anammox systems: Insights from electron donation and selective microbial enrichment - Jingwei Fu; Qian Li; Mawuli Dzakpasu; Yifei He; Pengyu Zhou; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

Anti-freeze hydrogel-based sensors for intelligent wearable human-machine interaction - Zhiwei Fu; He Liu; Qingying Lyu; Jingwei Dai; Ce Ji; Ye Tian (Chemical Engineering Journal, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Advanced low-strength wastewater treatment, side-stream phosphorus recovery, and in situ sludge reduction with aerobic granular sludge - Qiulai He; Xiaohui Yan; Zhiyi Xie; Peng Xu; Zhidong Fu; Jinfeng Li; Liang Liu; Peng Bi; Baokun Xu; Jingwei Ma (Bioresource Technology, 2023)

Performance of anaerobic/oxic/anoxic simultaneous nitrification, denitrification and phosphorus removal system overwhelmingly dominated by Candidatus_Competibacter: Effect of aeration time - Jingwei Ma; Yaning Ji; Zhidong Fu; Xiaohui Yan; Peng Xu; Jinfeng Li; Liang Liu; Peng Bi; Liang Zhu; Baokun Xu; Qiulai He (Bioresource Technology, 2023)

Step-wise SO2-feeding strategies for microalgae-based CO2 fixation from flue gas and bioenergy production - Yun Huang; Jingwei Fu; Ao Xia; Xianqing Zhu; Xun Zhu; Qiang Liao (Chemical Engineering Journal, 2023)

Precisely adjusting the organic/electrode interface charge barrier for efficient and stable Ag-based regular perovskite solar cells with >23% efficiency - Junlei Tao; Jingwei Xue; Hansong Guo; Yuhang Wang; Jinliang Shen; Tiening Wang; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2023)

Integrating wind-driven agitating blade into a floating photobioreactor to enhance fluid mixing and microalgae growth - Jingwei Fu; Hongyan Peng; Yun Huang; Ao Xia; Xianqing Zhu; Xun Zhu; Qiang Liao (Bioresource Technology, 2023)

Corrigendum to “Rapid start-up and stable operation of an aerobic/oxic/anoxic simultaneous nitrification, denitrification, and phosphorus removal reactor with no sludge discharge” [Bioresour. Technol. 362 (2022) 127777] - Qiulai He; Xiaohui Yan; Zhidong Fu; Yihang Zhang; Peng Bi; Xingliang Mo; Peng Xu; Jingwei Ma (Bioresource Technology, 2023)

Investigation of migration rule of rainwater for sponge city roads under different rainfall intensities - Zhe Qin; Yujing Yao; Jingwei Zhao; Houli Fu; Sheng Zhang; Liyuan Qiu (Environmental Geochemistry and Health, 2022)

Exploiting the gut microbiota to predict the origins and quality traits of cultured sea cucumbers - Zelong Zhao; Jingwei Jiang; Jie Zheng; Yongjia Pan; Ying Dong; Zhong Chen; Shan Gao; Yao Xiao; Pingzhe Jiang; Xuda Wang; Gaohua Zhang; Bai Wang; et al. (Environmental Microbiology, 2022)
Summary Nowadays, the true economic and nutritional value of food is underpinned by both origin and quality traits, more often expressed as increased quality benefits derived from the origin source. Gut microbiota contribute to food metabolism and host health, therefore, it may be suitable as a qualifying indicator of origin and quality of economic species. Here, we investigated relationships between the gut microbiota of the sea cucumber ( Apostichopus japonicus ), a valuable aquaculture species in Asia, with their origins and quality metrics. Based on data from 287 intestinal samples, we generated the first biogeographical patterns for A . japonicus gut microbiota from origins across China. Importantly, A . japonicus origins were predicted using the random forest model that was constructed using 20 key gut bacterial genera, with 97.6% accuracy. Furthermore, quality traits such as saponin, fat and taurine were also successfully predicted by random forest models based on gut microbiota, with approximately 80% consistency between predicted and true values. We showed that substantial variations existed in the gut microbiota and quality variables in A . japonicus across different origins, and we also demonstrated the great potential of gut microbiota to track A . japonicus origins and predict their quality traits.

RDF for temporal data management – a survey - Fu Zhang; Zhiyin Li; Dunhong Peng; Jingwei Cheng (Earth Science Informatics, 2021)

Impact of urbanization on hydrological processes under different precipitation scenarios - Wenbin Zang; Shu Liu; Shifeng Huang; Jiren Li; Yicheng Fu; Yayong Sun; Jingwei Zheng (Natural Hazards, 2019)

A haplotype in the CCR5 gene promoter was associated with the susceptibility to HIV-1 infection in a northern Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Xueyuan Jia; Chao Shen; Yanling Zhao; Yan Jin; Yang Yu; Hong Ling; et al. (Molecular Biology Reports, 2011)

CCR2-64I allele is associated with the progression of AIDS in a Han Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Yan Jin; Yang Yu; Feng Chen; Jing Bai; Hong Ling; Kaili Wang; et al. (Molecular Biology Reports, 2010)

Neuroprotective effects of safflor yellow B on brain ischemic injury - Chaoyun Wang; Dalei Zhang; Guisheng Li; Juntian Liu; Jingwei Tian; Fenghua Fu; Ke Liu (Experimental Brain Research, 2007)